Paediatric electroencephalography in sub-Saharan Africa: access to effective services, training capacity and applicability of teaching modules - Kander, Veena (Department of Paediatrics and Child Health, 2025)
Misinterpretation and misuse of an electroencephalogram (EEG) leads to misdiagnosis and unnecessary use of anti-seizure medication (ASM). This is prevalent in countries that lack qualified trained personnel to perform and interpret EEGs. Interpretation of paediatric EEGs is complicated, owing to brain maturation and many epilepsy syndromes manifesting from infancy to adolescence. This can be compounded if the EEG is not performed correctly, with technical artefacts mimicking abnormalities. Paediatric neurologists and neurologists are scarce in sub-Saharan Africa (SSA), as are trained paediatric technologists and technicians. This lack of specialised professionals exacerbates the difficulty of providing quality neurodiagnostic services and accessing essential care for paediatric patients, especially in SSA and other low income (LIC) and low middle income countries (LMIC). This thesis explored the question of who performs paediatric EEGs in SSA and whether they have the experience to report on these studies. The overall aim of this work was to establish a pedagogy in basic paediatric interpretation that could be used internationally to decrease existing gaps in paediatric EEG training. The study was divided into four chapters, with two additional chapters for the introduction and conclusion of the work. Chapter 1 presents the background and aim of the study, namely, to understand paediatric electroencephalography practice with the intent to develop tools to improve the ability to perform and deliver this service, especially in Africa. Chapter 2 presents a published systematic review analysing published reports critiquing EEG training programs accessible to non-specialist clinicians worldwide, over a 30-year period. Chapter 3 provides information from a web-based survey exploring who performs and interprets EEG studies in SSA. Chapter 4 provides information based on the use of an EEG training handbook, from a web-based survey of 50 participants who registered for the online course. Chapter 5 presents qualitative data from 15 experts on training non-epilepsy specialists in paediatric EEG interpretation. In chapter 6, I conclude the correlation of data provided from the four articles. There is a need for critiqued training resources to enable non-epilepsy specialists to utilise EEG. This healthcare cadre is considered to be appropriate with adequate support to perform this role, and the EEG training handbook was found to be a useful tool to teach non-epilepsy specialists in paediatric EEG interpretation, thus further bridging the knowledge gap in SSA.